Development of high average power lasers for the photon collider - Gronberg, J; Stuart, B; Seryi, A (2010)
The laser and optics system for the photon collider [1] seeks to minimize the required laser power by using an optical stacking cavity [2, 3] to recirculate the laser light. An enhancement of between 300 to 400 is desired. In order to achieve this the laser pulses which drive the cavity must precisely match the phase of the pulse circulating within the cavity. We report on simulations of the performance of a stacking cavity to various variations of the drive laser in order to specify the required tolerances of the laser system.